Cantigas e brincadeiras de roda: análise do desenvolvimento musical de crianças da pré-escola em São Luís-Maranhão - SOUSA, Adriana Rodrigues de (2022)
This study sought to investigate children's culture as a vehicle for children's musical development and learning. It dealt with the concepts and visions about the songs and wheel games, and how music is intertwined with children's culture, that is, with the world of children. The main musical characteristics found in traditional songs and games are pointed out in the theoretical reference of this text. In these lines, we sought to highlight the need for these manifestations to be present in the school space and their importance in the education of young children and their benefits. Studies on musical development made up the body of this dissertation, in which theories considered valid in the field of music education and musical cognition were highlighted. The research problem is defined by the following question "How do nursery rhymes and games contribute to the musical development of preschool children? As a hypothesis we have that the experience of the songs and games promote the development of musical abilities and learning. The general objective is "to verify how nursery rhymes and games contribute to the musical development of preschool children, based on the experience of the activities in school space". The justification for the development of this research lies in finding in the literature several benefits related to children's nursery rhymes and games as promoters of social and affective relationships and of various types of learning. Thus, it is considered, mainly, the importance of these activities for the musical development of young children, contributing to the construction of musical concepts.